Numerical Modeling and Analysis of Shadow Flicker Using Solar Path Functions for Enhanced Predictive Accuracy - Nicolai Radke; Patrick E. M. De Smet; Erika Ábrahám (Energies)
Shadow flicker caused by wind turbine blades passing through sunlight can significantly affect nearby residential buildings, raising environmental and regulatory concerns in wind farm development. The accurate assessment of shadow flicker exposure is critical for compliance and minimizing community impacts. We present a novel method for accurately determining the exposure of shadow flicker from wind turbines on residential buildings, addressing a key regulatory concern in wind farm planning. Current simulation techniques rely on discrete sampling of solar positions, resulting in potential inaccuracies tied to sampling resolution. Our proposed approach models shadow flicker as a continuous function and applies numerical minimization and numerical root finding to compute the duration of exposure. Our evaluation proves that this method achieves a superior balance between precision and computational efficiency, significantly improving existing techniques.